Stand evaluation, crop estimation and yield analysis of winter wheat for the optimization of yields - Pap, Nárcisz; Pap, János; Schmidt, Rezső (Acta Agraria Debreceniensis, 2019)
The authors have been carrying out stand evaluation, crop estimation and yield analysis in winter wheat since 2012. The sampling areas were assigned at the fields of the Training Farm of the Faculty of Agricultural and Food Sciences of Széchenyi István University Mosonmagyaróvár according to the structure of the cropping system. According to their observations the value of field emergence is always lower than the laboratory germination. The weak emergence is important because the lower plant density cannot be compensated by the increased tillering in spite of having larger plant growth space. It is proven by the fact that they detected strong productive tillering even at 5 and 10 mm plant spacing while there were single-spiked plants at 40-50 mm plant spacing as well. The analysis revealed that the total ear mass and grain mass of wheat plants bearing two or more ears is almost the double than that of the single-spiked plants. It was a further basic experience that the largest ear of ”multiple-spiked” plants is always heavier than the single ear of one-spiked plants. Plants with intense tillering and more ears demonstrate the importance of proper seedbed preparation and drilling and the significance of sowing good quality seeds. These are the factors that determine field germination and emergence, influence the speed and intensity of initial development and by all these factors the sufficient productive tillering. The authors emphasize the use of exact and objective methods at crop estimation, e.g. the relationship between the ear mass and the yield which is in strong correlation whilst ear length and grain mass are not suitable for a precise estimation. The authors conclude that crop estimation and yield analysis must be inevitable tools of modern crop production and will be particularly important in precision agriculture. These tools also qualify the job done by farmers and helps to identify the areas that require special attention.